A confirmatory and an exploratory factor analysis of the Cohen-Mansfield Agitation Inventory (CMAI) in a european case series of patients with dementia: Results from the RECage Study - Cesana, Bruno Mario; Poptsi, Eleni; Tsolaki, Magda; Bergh, Sverre; Ciccone, Alfonso; Cognat, Emmanuel; Fabbo, Andrea; Fascendini, Sara; Frisoni, Giovanni B.; Frölich, Lutz; Jori, Maria Cristina; Mecocci, Patrizia; et al. (Brain Sciences, 2023)
Background: One of the most widely used instruments for assessing agitation in dementia patients is the Cohen-Mansfield Agitation Inventory (CMAI), nevertheless no global score has been proposed. The aim of this study is: (a) to conduct a confirmatory (CFA) and exploratory factor analysis (EFA) of CMAI on people with dementia and Psychological and Behavioral Symptoms (BPSD), and (b) to propose an alternative structure, based on clinical criteria including all CMAI items. Methods: Confirmatory and exploratory factor analyses were carried out on the CMAI 29 items administered at baseline to 505 patients with dementia (PwD) and BPSD enrolled in the international observational RECage study. Results: The three-factor structure has not been confirmed by the CFA, whilst the EFA was carried out respectively on 25 items disregarding 4 items with a prevalence ≤5% and then on 20 items disregarding 9 items with a prevalence ≤10%. The four-factor structure explaining 56% of the variance comprised Physically Aggressive behavior, Verbally Aggressive behavior, Physically non-aggressive behavior, and Physically and verbally aggressive behavior. Conclusions: A new grouping of all items according to a clinical criterion is proposed, allowing for a more sensible evaluation of the symptoms leading to better differentiation.